Znanje in odnos do vode na začetku drugega triletja osnovne šole - Rajšp, Martina (Revija za elementarno izobraževanje, 2011)
Knowledge of and Relationship to Water in Fourth and Fifth Grade. In the article analyzed water and its significance. This was accomplished by consulting analyses of scientific and technical literature from both domestic and foreign sources. We carefully reviewed the national curriculum for the subject Natural and Technical Science in 4th and 5th grade and its relation to water. The results of the survey, which included 154 students from 4th and 5th classes, revealed that the students have satisfactory knowledge about water. Parents and schools play an important role in forming pupils’ attitude towards water.
Keywords: water; primary school; Natural and Technical Science; knowledge; attitude